Dose estimation and calculation of radiological hazard index at Doce River / Brazil due to Fundão dam rupture - Roberto Ferreira Carmo; Heitor Evangelista; José Ubiratan Delgado; Octávio Luis Trindade Filho; Araceli Verónica Flores Nardy Ribeiro; Joselito Nardy Ribeiro; Madsom de Godoi Pereira; Marcus Vinícius Licínio (Brazilian Journal of Radiation Sciences)
The monitoring of the activity of radionuclides of natural occurrence as 238U, 232Th, 226Ra, 40K including 210Pb is important to assess the radiological impact and human exposure due to radioactivity in estuaries. In the case of the Doce River, a mining activity and a strong use of soil on its banks continued for decades. This river suffered a serious accident at 2015 due to a rupture of a tailings dam in your upper course, characterizing it as the biggest Southern Hemisphere accident in the mineral area. This work determined the radioactivity levels in sediments of the Doce River estuary from samples collected before and after the rupture. The concentrations analyzed by gamma spectrometry with Ge detector for 238U, 232Th, 226Ra, including  210Pb  and 40K  in sediments, ranged from [(15.86 ± 0.99), (19.83 ± 1.10), (55.65 ± 7.71), (11.58 ± 4.43) and (237.15 ± 8.70)] Bq kg-1 before the breakup, respectively, for [(20.70 ± 0.99) (31.82 ± 1.30), (90.84 ± 8.50) (11.41 ± 4.04) and ( 197.50 ± 7.62)] Bq kg-1, in the period after the breakup, respectively. This study identified an increase in 238U, 232Th and 226Ra concentrations after the rupture. It was evaluated the annual effective dose equivalent to the local population and the radiological risks, both internal and external, second model UNSCEAR. The results obtained for the radiological risk on the local population were compared with the world values obtained in similar environments for these radionuclides.